Differentiate y = (3x − 2)^4

  • Google+ icon
  • LinkedIn icon
  • 803 views

We recognise that this is in the form of a function within a function, i.e u= 3x - 2 is within the u^4 function, therefore here we will use the chan rule to differentiate the equation. 

The chain rule states that dy/dx = dy/du * du/dx.

Here let u = 3x -2, then du/dx = 3. Similarly, y=u^4 so dy/du = 4u^3. Therefore dy/dx = 3 * 4u^3 = 12u^3.

Finally, we substitute u = 3x - 2 into the equation. This therefore gives us, dy/dx = 12(3x - 2)^3.

Wajiha I. A Level Maths tutor, GCSE Maths tutor

About the author

is an online A Level Maths tutor with MyTutor studying at Manchester University

Still stuck? Get one-to-one help from a personally interviewed subject specialist.

95% of our customers rate us

Browse tutors

We use cookies to improve your site experience. By continuing to use this website, we'll assume that you're OK with this. Dismiss

mtw:mercury1:status:ok